PENGARUH PENYULUHAN PENGGUNAAN ANTIBIOTIKA TERHADAP TINGKAT PENGETAHUAN MASYARAKAT DI KOTA MANADO - Wowiling, Chalvy; Goenawi, Lily Ranti; Citraningtyas, Gayatri (PHARMACON, 2013)
ABSTRACT The high number of inappropriate of antibiotics in community due to lack of knowledge about the use of antibiotics may lead the increasing of antibiotic resistance. This study aimed to measure the people’s knowledge before and after following health education and analyze the effect of health education of antibiotic administration to community knowledge. This is a pre-experimental study in community with one group pretest-posttest design using a questionnaire. Result of this study show the number of respondent with lack of knowledge before the education is 53,3% decrease after education which is 17,3%, number of respondent with quite good increase from 37,3% become 42,7%, and respondent with good knowledge increase from 9,3% become 40%. Mean of knowledge score after following health education 70,53 is higher than before following health education 55,53, so H1 is accepted with significant value 0.000 (p<0,05). Health education can increase public knowledge about antibiotic administration. Keywords : antibiotic, health education , people of Manado City